2020
DOI: 10.1093/ehjci/jeaa194
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid valve geometry and right heart remodelling: insights into the mechanism of atrial functional tricuspid regurgitation

Abstract: Aims  We sought to investigate tricuspid valve (TV) geometry and right heart remodelling in atrial functional tricuspid regurgitation (AF-TR) as compared with ventricular functional TR with sinus rhythm (VF-TR). Methods and results  Transoesophageal 3D echocardiography datasets of the TV and right ventricle were acquired in 51 symptomatic patients with severe TR (AF-TR, n = 23; VF-TR, n = 28). Three-dimensional right ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…Atrial fibrillation patients with FTR showed increased TA tenting volumes compared with controls, which is associated with a reduction in the coaptation height, suggesting that the increase in tenting volume was mostly a result of the enlarged TA and less related to leaflet tethering. Even more, our results are consistent with data obtained by Utsunomiya et al 27 in patients with AF and severe FTR. They reported that, despite similar severity of FTR, patients with atriogenic FTR had more dilated and posteriorly displaced annulus and less leaflet tethering angles with larger RA and smaller RV end-systolic volumes compared with ventricular FTR.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Atrial fibrillation patients with FTR showed increased TA tenting volumes compared with controls, which is associated with a reduction in the coaptation height, suggesting that the increase in tenting volume was mostly a result of the enlarged TA and less related to leaflet tethering. Even more, our results are consistent with data obtained by Utsunomiya et al 27 in patients with AF and severe FTR. They reported that, despite similar severity of FTR, patients with atriogenic FTR had more dilated and posteriorly displaced annulus and less leaflet tethering angles with larger RA and smaller RV end-systolic volumes compared with ventricular FTR.…”
Section: Discussionsupporting
confidence: 94%
“…Our data are also concordant with recently reported findings by Ortiz-Leon et al 7 who showed that, in patients without severe FTR, AF was associated with RA and TA remodeling independently of the presence of left heart diseases and that the size of the TA correlated with RAVmax but not with RV volumes. We were able to assess the dynamic function of both the TA and RA, and we added significantly to the results of Utsunomiya et al 27 and Ortiz-Leon et al 7 by showing that the main determinants of FTR severity were the TA area at end diastole and RAVmin in a population including patients with mild, moderate, and severe FTR. The RAVmin, measured at end diastole, when the maximum TA area was measured, showed the strongest correlation with TA area.…”
Section: Discussionmentioning
confidence: 99%
“…TV annulus is considerably enlarged in AF patients, even with less than severe FTR, and independently of the presence of cardiac structural abnormalities, supporting that TA dilation is the direct consequence of AF itself, rather than the result of FTR 26 . Compared with ventricular FTR patients and for similar FTR severity, patients with atrial FTR had increased dimensions and posterior displacement of the TV annulus, larger RA, and smaller RV 6 . Moreover, in patients with so-called "idiopathic FTR" (most of them being actually atrial FTR due to AF), Topilsky 27 observed that the RV assumes a triangular shape with dilation occurring at the basal level, resulting in a large TV annular area without leafl et tethering (Figure 1).…”
Section: Anatomy and Pathophysiologymentioning
confidence: 90%
“…Once the pathophysiological cascade is initiated (either by ventricular or atrial factors), a vicious cycle ensues, with progressive FTR and further dilatation of the TA due to either RA or RV volume overload, resulting in further FTR and ultimately a combination of both atrial and ventricular FTR 4,28,29 . Therefore, in advanced stages with massive or torrential FTR, marked remodeling of TV apparatus, and secondary RA and RV dysfunction due to longstanding volume overload, it may be more challenging to distinguish the primary cause of FTR 6,16 . However, the prognosis of massive/torrential FTR is severe 30,31 and there is likely little clinical benefi t in clarifying the pathophysiological sequence at this advanced stage of the disease.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation